2017
DOI: 10.1051/e3sconf/20171901040
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of mixtures of mineral oil and natural ester in terms of their application in the transformer

Abstract: Abstract. The article describes research results of thermal properties of mineral oil and natural ester. Percentage proportions of both the liquids were as follows: 100/0, 95/5, 80/20, 50/50, 20/80, 0/100. The authors present measurement results of thermal conductivity, viscosity, specific heat, density, and thermal expansion of the created mixtures. The measurements were taken in a relatively wide temperature range: 25 ºC, 40 ºC, 60 ºC, and 80 ºC. On the basis of the measurement results, convection heat trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…The conductivity and viscosity depend to a significant extent on the temperature, and thus they affect other properties of the insulating liquids, which include the carrier mobility, molecular diffusion coefficient, relative dielectric constant, and charge relaxation time. The relative dielectric constant influences the stress distribution in a transformer's insulation system, and thus it determines its electric durability [26][27][28]. When analyzing the data contained in Tables 1 and 2, it can be observed that the ageing processes affect to a different extent the physicochemical and electrical properties of Trafo EN mineral oil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conductivity and viscosity depend to a significant extent on the temperature, and thus they affect other properties of the insulating liquids, which include the carrier mobility, molecular diffusion coefficient, relative dielectric constant, and charge relaxation time. The relative dielectric constant influences the stress distribution in a transformer's insulation system, and thus it determines its electric durability [26][27][28]. When analyzing the data contained in Tables 1 and 2, it can be observed that the ageing processes affect to a different extent the physicochemical and electrical properties of Trafo EN mineral oil.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed that the content of the mixture significantly determines the change of the tested parameters. Nadolny et al [27,28] presented the research results of thermal properties of Nytro Taurus mineral oil with Envirotemp FR3 natural ester and Midel 7131 synthetic ester mixtures. The authors showed the measurement results of thermal conductivity, viscosity, specific heat, density, and thermal expansion of the created mixtures in a wide temperature range.…”
Section: Research Of Insulating Liquids Mixturesmentioning
confidence: 99%
“…An acoustic pressure source modeled on the geometry of the Sonalleve V R V2 transducer (shown in Figure 3) was used. 4178 [17] 1974 [59] 3421 [17] 2348 [17] 1312 [17] 1004 [17] Sound speed, density and attenuation values for air are explained in the text.…”
Section: Acoustic Simulationmentioning
confidence: 99%
“…The transformer windings are located in a dielectric fluid that provides both insulation and winding cooling. Mineral oil, silicone fluid, synthetic or natural esters can be used as a dielectric fluid (CIGRE, 2010;Nadolny & Dombek, 2017;Njombog Tanteh et al, 2014). Experimental studies indicate that the cooling capacity of the alternative liquid worsens with aging due to the exponential decrease of the viscosity with temperature (Ortiz et al, 2018).…”
Section: Passive Cooling With Liquid Heat Transfer Fluidmentioning
confidence: 99%